Design and Validation of an Educational Model for the Application of Technology in Philosophy Program for Children for Gifted Students - Esmael Zarraii zavaraki; aliakbar kabiri; yahya hgaedi; ali delavar; mohammadreza nili ahmadabadi (Ravānshināsī-i Afrād-i Istis̠nāyī, 2021)
The aim of this study was to identify the components and framework of the educational model for the use of technology in philosophy program for children for gifted students and its internal validation. The research method was heuristic. In order to obtain the educational design model, inductive content analysis was used in the qualitative part of the research, and in the quantitative part, survey method was used to validate the model internally through a questionnaire by experts. The sample population of the study in the qualitative part were related specialists in the fields of educational technology, special education and philosophy of education, written and electronic documents and resources, and in the quantitative part were the specialists of the mentioned fields. The samples were purposefully selected in both groups, and in the qualitative part 31 specialists and experts were selected for the interview and in the quantitative part 36 specialists from different universities and institutes of the country. Data were collected in the qualitative part using semi-structured interviews and content analysis of documents and in the quantitative part using a questionnaire made by the researcher. After conducting content analysis, 7 main categories were obtained. Also, 39 sub-components were extracted for the main categories. After extracting the codes, the components and sub-components were presented in the form of a model. The results of internal validation based on the opinion of experts have shown that the presented educational model has a good internal validity and has the necessary effectiveness to educate talented students.